Isolasi Kolagen Dari Kulit Dan Tulang Ikan Cakalang (Katsuwonus pelamis) - Stephanie TW Ata , Risfah Yulianty, Fitriyanti J. Sami , Naimah Ramli (STIFA Makassar, 2016)
Collagen is a type of protein that is contained in the body of an animal with a proportion of about 30 % of the total protein in the body as a whole . Skin and bones of fish can be used as an alternative source of collagen to replace the collagen from animals such as cattle. Concerning the issue about Bovine Spongiform Encephalopathy ( BSE ) disease, the swine flu as well as halal standard product. The main objective of this study was to isolate collagen and determine the amount of collagen derived from skin and bones skipjack tuna fish. Skipjack tuna fish skin and bones extracted by immersion using 0.5 M acetic acid solution to obtain a filtrate futhermore precipitated and dried with a spray dryer to obtain a dry collagen . The results showed that the collagen can be isolated from skipjack tuna with a percentage value amounted to ranging from 14.48% collagen of skin and 16.71 % collagen of skipjack tuna